Exploration and practice of teaching methods of basic specialized courses for postgraduate majors based on the characteristics of “Three Teaching Processes” - Zhang, Youhong; Chang, Xinlong; Yue, Chunguo; Li, Linyuan (SHS web of conferences, 2023)
The ability of engineering graduate students to use their knowledge and independently engage in scientific research is one of the important indicators to measure the quality of postgraduate training. This paper takes the comprehensive improvement of graduate students’ ability to engage in scientific research independently as the starting point, and improves the teaching quality of basic courses of graduate majors in an all-round way by constructing teaching methods of basic knowledge intensive teaching, knowledge application and case process teaching, so that students can deeply grasp the course knowledge system and flexibly apply the knowledge learned in the course learning process. Finally, it lays a good foundation for students to engage in scientific research independently.